2017
DOI: 10.1111/acel.12603
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the ribosomal RNA gene promoter is associated with aging and age‐related decline

Abstract: SummaryThe transcription of ribosomal RNA genes (rDNA) is subject to epigenetic regulation, as it is abrogated by the methylation of CpG dinucleotides within their promoter region. Here, we investigated, through Sequenom platform, the age‐related methylation status of the CpG island falling into the rDNA promoter in 472 blood samples from 20‐ to 105‐year‐old humans and in different tissues (blood, heart, liver, kidney, and testis) of 15 rats 3–96 weeks old. In humans, we did not find a consistently significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 49 publications
8
54
2
Order By: Relevance
“…The negative effects of aging on protein synthesis and energy metabolism are major hallmarks of aging (López‐Otín et al, 2013). The aging process in many organisms is associated with alterations of the ribosome biogenesis, an overall decline of protein synthesis and the age‐related reduction of rRNA expression (D'Aquila et al, 2017), suggesting that both RNA polymerase II‐ and III‐dependent transcription are affected. The ribosomal protein and RNA expression are controlled by the mTOR pathway (Iadevaia, Liu, & Proud, 2014), although we could not demonstrate the decreased mTOR activity in aged monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of aging on protein synthesis and energy metabolism are major hallmarks of aging (López‐Otín et al, 2013). The aging process in many organisms is associated with alterations of the ribosome biogenesis, an overall decline of protein synthesis and the age‐related reduction of rRNA expression (D'Aquila et al, 2017), suggesting that both RNA polymerase II‐ and III‐dependent transcription are affected. The ribosomal protein and RNA expression are controlled by the mTOR pathway (Iadevaia, Liu, & Proud, 2014), although we could not demonstrate the decreased mTOR activity in aged monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was shown that the levels of total mRNA, as well as the expression of RNA polymerase I, eIF2Bε and eEF2, decrease with age in rat tissues (10). Increased promoter methylation in ribosomal RNA genes and decreased ribosomal RNA concentration during aging were also reported (11). In addition, down-regulation of translation with age was confirmed in vivo in the sheep (12) as well as in replicatively old yeast (13).…”
Section: Introductionmentioning
confidence: 84%
“…To characterize age-related changes in protein synthesis, we subjected mouse tissue samples to both transcriptome sequencing and ribosome profiling (Table S1), as this approach allows to separate the contribution of transcription and translation processes. Liver samples were collected from male mice representing six age groups (1,3,11,20,26 and 32 months old), and kidney samples from three age groups (3, 20 and 32 months old) ( Fig. 1A).…”
Section: Gene Expression Changes In Mouse Liver and Kidney Reflect Agmentioning
confidence: 99%
“…In this study, we successfully sequenced, cloned, and characterized SPB18S , enabling the generation of transgenic plants expressing appropriate dsRNA for silencing this critical gene in a major insect pest. Among eukaryotes, 18S rDNA is highly conserved (D'Aquila et al., ; Ianni, Hoelper, Krueger, Braun, & Bober, ). Our comparisons of the Spb18S dsRNA target region with homologous sequences from soybean, bees, and humans revealed the lack of any continuous 10‐nucleotide (nt) matches ().…”
Section: Discussionmentioning
confidence: 99%